Mapping the Scholarship of Fake News Research: A Systematic Review - Abu Arqoub, Omar; Elega, Adeola Abdulateef; Efe ozad, Bahire; Dwikat, Hanadi; Oloyede, Felix Adedamola (Routledge Journals, Taylor & Francis Ltd, 2022)
This study empirically examined studies on fake news through a content analysis of 103 peer-reviewed articles obtained from the eight major databases. The articles were published between 2000 and 2018. This systematic review of the journals, progression, theories, methodologies, media genres, common used words, and geospatial distribution indicated that the majority of the articles were published in Journalism Practice, Popular Communication, Digital Journalism, and Journalism Studies. Regarding progression, the highest number of publications was recorded for 2017 and 2018. At least one article was published each year beginning in 2005; 2006 and 2014 were exceptions. The results indicate that the majority of the articles were atheoretical. Qualitative research methods, content analysis, and surveys which were applied oftentimes. The studies were equally distributed across all media genres (traditional, digital, and social media). However, television and Twitter were the platforms that received the greatest amount of scholarly attention. The articles focused on the United States more than any other country. Finally, news, media, and fake were the most regularly frequently occurring words.
Keywords: Fake news; fake news research; content analysis; text mining; systematic review; Journalism